Students' perceptions of an internationalised learning environment - Quintal, Vanessa; Phau, Ian (Emerald Group Publishing Limited, 2014)
Purpose – The purpose of this paper is to explore student perceptions of the internationalised learning environment across a particular university's home and offshore campuses. It addresses three research questions namely: what constitutes the internationalised learning environment for students? Can a university offer an internationalised learning environment that is equitable for students across its home and offshore campuses? And what differences exist in the internationalised learning environment for students in a university's home and offshore campuses?Design/methodology/approach – In total, 484 completed responses were collected from the university's six campuses in Australia, Singapore, Hong Kong and Malaysia.Findings – Findings suggested significant differences in the way students perceived of teaching reputation, context-specific curriculum, resources, student-support staff interaction and their attitude towards their university.Practical implications – These insights could help a university's teaching staff and administrators to focus on specific attributes in marketing the internationalised learning environments of each of its campuses. This could give the university better opportunity for improving the learning process and its outcomes for students.Originality/value – This paper sets out to define the parameters of the internationalised learning environment and conducts an audit of this environment from the student perspective. Findings suggested significant differences in the way students perceived of teaching reputation, context-specific curriculum, resources, student-support staff interaction and their attitude towards their university. In the market of fierce competition for international students, it is crucial that these positive attributes be part of the marketing messages in any promotion campaigns for universities.